Tambua Tansa Performance Form By Sanggar Shimpony Badantiang In Nagari Lubuk Basung, West Sumatera - Fikratul, Nesa Ulya; Anggraini, Nora; Munafri, Sastra (Institut Seni Indonesia Padangpanjang, 2024)
Tambua Tansa is a Minangkabau tradition passed down from generation to generation in West Sumatra. One area that still pays attention to the existence of Tambua Tansa is Lubuk Basung, under Sanggar Shimpony Badantiang, founded by Marisha Isman in 2012. The focus of this research is on the form of Tambua Tansa performance developed by Sanggar Shimpony Badantiang, as well as the existence of this studio in Nagari Lubuk Basung. This research uses qualitative research methods, using a theoretical approach to performance forms and existence theory as supporting theories in examining the existence of Sanggar Shimpony Badantiang. The characteristics of the Tambua Tansa game use simple musical motifs which are then developed into songs. The songs that are often played in performances are divided into two songs, namely; Pangka Matam and Atam Panjang. The existence of Sanggar Shimpony Badantiang has been able to be maintained until now due to good organizational governance as well as creativity and innovation carried out by artists.